The Effect of Phytobiotic, Zinc, and their Combination in the Diet on Broiler Carcass Quality - Muhammad Nur Hidayat (Jurnal Sain Peternakan Indonesia, 2022)
This study aimed to determine broilers' final body weight and carcass quality given herbs Temulawak (Curcuma zanthorrhiza) flour and Kencur (Kaempferia galangal) flour and zinc mineral. The research design was completely randomized with five treatments and four replications, each containing three broilers aged one day. The treatments (P) given included P1 (basal ration), P2 (basal ration + 2.5% Temulawak flour + 120 ppm mineral zinc), P3 (basal ration + 0.4% Kencur flour + 120 ppm mineral inc), P4 (basal ration + 2.5% Temulawak flour + 0.4% Kencur flour), and P5 (basal ration + 2.5% Temulawak flour + 0.4% Kencur flour + 120 ppm mineral zinc). The analysis of variance showed that the treatment had a significant effect (P<0.05) on final body weight, carcass weight, percentage, and carcass. But no significant effect (P>0.05), boneless percentage, bone percentage, meat and bone ratio, and abdominal fat. The combination of Kencur and zinc in the ration (P3) showed the best results in improving final body weight and carcass quality, including carcass weight. The provision of Temulawak flour and Kencur flour and the addition of zinc minerals to the feed did not negatively affect carcass quality.